Industrial Dust and Its Effects on the Human Body - N. M. Bakhriddinova (Peerian Journals Publishing, 2022)
The work studied the classification of types of industrial dust. An event to combat industrial dust. The characteristic of the impact of dust on the human body, which can be the cause of diseases, is given. Methods and means of protection against dust are widely covered
Keywords: Occupational diseases; harmful factors; industrial dust; silicosis